Criminal defense and judicial sentencing in China's death penalty cases - Xiong, Moulin (Psychology, crime & law, 2018)
Drawing upon 503 cases of violent and drug crimes involving the death penalty from three intermediate courts in China, this study explores various defense arguments, their acceptance rates, and factors that influence judicial sentencing. Our findings reveal that offenders’ post-crime good behaviors are most likely to be accepted by the court, thus helping offenders obtain suspended death penalty. In contrast, being charged with multiple violent crimes and the weight of narcotics in drug crimes are two significant factors related to an increased likelihood of receiving immediate death penalty. This article provides more empirical evidence about mitigating and aggravating circumstances considered in capital sentencing, and supports that private lawyers are not different from court appointed lawyers in China's capital defense. China's current system seemingly leaves little room for defense lawyers to make creative contributions.